Reinsurance in the Supplementary Health: A Counterfactual Study on the Impacts of Reinsurance Treaties Adoption by Healthcare Plans Operators in Brazil - Caio Alexandrino Costa Areias; João Vinícius de França Carvalho (BBR: Brazilian Business Review)
The sustainability of the Brazilian Supplementary Health System has been frequently debated, since the number of operators has decreased considerably in recent years after bankruptcy records. In this context, risk transfer mechanisms are presented as options for financial loss mitigation and asset protection. Reinsurance is one of them, but, due to legal understandings, its adoption has been restricted to insurance companies since 2009 and forbidden for other types of operators, such as cooperatives, self-management, and philanthropic enterprises. Using industry microdata and applying the collective risk theory, implemented by the classic ruin model (Cramér-Lundberg), this study aimed to counterfactually verify how reinsurance would impact operators solvency in a hypothetical long-term scenario in which all of them had access to these tools. By introducing quota share, with retentions of 60% and 80% of the aggregate expenses, and Stop-Loss treaties, with retention limits of 80% and 95%, it was verified that the ruin probability decreased in the first case by around 40% and 20%. However, the adoption of Stop-Loss for aggregate expenses increased the need for solvency capital, as a result of its higher premiums, becoming viable when directed to higher cost events.